Legal Protection in Indonesia's Cyber Resilience: Strategy and Implementation to Support National Defense - Priyanto (Faculty of Law, Universitas Pekalongan, 2024)
Legal protection and cyber resilience strategies in Indonesia are important issues considering the increasingly complex cyber threats that threaten national security. This study aims to analyze the relationship between legal protection strategies and cyber resilience, as well as the role of policy, technology, and international cooperation in strengthening Indonesia's cyber resilience. The type of research used is qualitative research with a case study approach. The research population consists of experts and practitioners in the fields of law and information technology, with a purposive sampling technique. The number of samples taken was 15 respondents, including government officials, cyber security practitioners, and related academics. This research was conducted in Jakarta for six months. The results of the study indicate that clear legal policies and harmonization of domestic and international policies are very important in strengthening cyber resilience. In addition, the implementation of effective legal policies, increasing institutional capacity, and more intensive international cooperation can accelerate the response to cyber threats. Advanced technologies, such as artificial intelligence and big data, also play an important role in detecting and responding to threats in real time. The implications of this study are the importance of strengthening adaptive regulations and synergy between institutions in building more resilient cyber resilience in Indonesia.